Resistance exercise reduces kynurenine pathway metabolites in breast cancer patients undergoing radiotherapy - Zimmer, Philipp; Schmidt, Martina; Prentzell, Mirja Tamara; Berdel, Bianca; Wiskemann, Joachim; Kellner, Karl Heinz; Debus, Jürgen; Ulrich, Cornelia; Opitz, Christiane A.; Steindorf, Karen (Frontiers in oncology, 2019)
Purpose: Evidence from preclinical studies and trials in healthy volunteers suggests that exercise may modulate the levels of tryptophan (TRP) metabolites along the kynurenine (KYN) pathway. As KYN and downstream KYN metabolites are known to promote cancer progression by inhibiting anti-tumor immune responses and by promoting the motility of cancer cells, we investigated if resistance exercise can also control the levels of KYN pathway metabolites in breast cancer patients undergoing radiotherapy (NCT01468766). Patients and Methods: Chemotherapy-naïve breast cancer patients (n = 96) were either randomized to an exercise/intervention group (IG) or a control group (CG). The IG participated in a 12-week supervised progressive resistance exercise program twice a week, whereas the CG received a supervised relaxation program. Serum levels of TRP and KYN as well as urine levels of kynurenic acid (KYNA) and neurotoxic quinolinic acid (QUINA) were assessed before (t0), after radiotherapy, and mid-term of the exercise intervention (t1) and after the exercise intervention (t2). Additionally, 24 healthy women (HIG) participated in the exercise program to investigate potential differences in its effects on KYN metabolites in comparison to the breast cancer patients. Results: At baseline (t0) the breast cancer patients showed a significantly elevated serum KYN/TRP ratio and urine QUINA/KYNA ratio, as well as increased urine QUINA levels in comparison to the healthy women. In response to exercise the healthy women and the breast cancer patients differed significantly in the levels of urine QUINA and the QUINA/KYNA ratio. Most importantly, serum KYN levels and the KYN/TRP ratio were significantly reduced in exercising patients (IG) compared to non-exercising patients (CG) both at t1 and t2. Conclusion: Resistance exercise may represent a potent non-pharmacological avenue to counteract an activation of the KYN pathway in breast cancer patients undergoing radiotherapy.
Gesehen am 04.02.2020